1997
DOI: 10.1097/00000539-199706000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Morphine Analgesia in Chronic Pain Patients with Osteoarthritis

Abstract: Controlled clinical studies have shown that local administration of morphine can significantly relieve acute postoperative pain. This analgesic effect is long-lasting (up to 48 h) and is mediated by peripheral opioid receptors. Experimental evidence shows that analgesic effects of peripheral opioids and the density of opioid receptors on peripheral sensory nerves increase with the duration of painful inflammatory processes. This study examines the analgesic effects of 1 mg of morphine injected into the arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 18 publications
1
39
0
3
Order By: Relevance
“…Therefore, the peripheral administration of opioid agonists may, theoretically, inhibit the chronic pain of infl ammation under ischemic conditions in PVD. Locally administered opioids have been shown to elicit effective analgesic effects in various acute and chronic clinical pain syndromes, including burn pain [27], infl ammatory pain [28], osteoarthritis [7], and rheumatoid arthritis [29], as well as after dental [11], urinary bladder [30], and knee surgery [31], too. In the present study we used morphine as an adjunct to bupivacaine through a popliteal catheter in chronic pain due to PVD, based on the interaction between opioids and infl ammatory conditions and also based on clinical trials as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the peripheral administration of opioid agonists may, theoretically, inhibit the chronic pain of infl ammation under ischemic conditions in PVD. Locally administered opioids have been shown to elicit effective analgesic effects in various acute and chronic clinical pain syndromes, including burn pain [27], infl ammatory pain [28], osteoarthritis [7], and rheumatoid arthritis [29], as well as after dental [11], urinary bladder [30], and knee surgery [31], too. In the present study we used morphine as an adjunct to bupivacaine through a popliteal catheter in chronic pain due to PVD, based on the interaction between opioids and infl ammatory conditions and also based on clinical trials as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that perineural opioids on top of local anesthetics prolong postoperative analgesia and that this kind of analgesia is mediated by peripheral opioid receptors [5][6][7][8][9]. These peripheral analgesic effects of opioids are predominant under infl ammatory conditions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic pain states such as rheumatoid and osteoarthritis, intra-articular morphine injections elicited pain relief of longer duration (up to 7 days) [32,33]. This may be the result of analgesic and anti-inflammatory effects of locally applied opioids.…”
Section: Intra-articular Administrationmentioning
confidence: 99%
“…Likar et al [32] could show that a single dose of 1-mg intra-articular morphine into the knee joint of patients with chronic osteoarthritis resulted in a significant reduction in pain intensity at rest and during movement with a longlasting effect up to 1 week. Similar results were seen by Stein et al [33] who were treating patients with rheumatoid arthritis or osteoarthritis.…”
Section: Intra-articular Administrationmentioning
confidence: 99%
“…In humans, the local (i.a.) injection of small, systemically inactive doses of morphine has been shown to produce potent analgesia in acute and chronic arthritis (e.g., knee surgery, rheumatoid and osteoarthritis) [7][8][9][10]. As a result, several medical societies have meanwhile adopted i.a.…”
Section: Discussionmentioning
confidence: 99%